Visual stimuli in the peripersonal space facilitate the spatial prediction of tactile events—A comparison between approach and nearness effects - Kimura, Tsukasa; Katayama, Jun'ichi (Frontiers in Human Neuroscience, 2023)
Previous studies reported that on object in one’s peripersonal space (PPS) attracts attention that facilitates subsequent processing of stimuli. Recent studies showed that visual stimuli approaching the body facilitated the spatial prediction of subsequent tactile events, even if these stimuli were task-irrelevant. However, it is unclear whether the approach is important for facilitating this prediction or if the simple existence of stimuli within the PPS is what matters. The present study aimed to scrutinize the predictive function of visuo-tactile interaction in the PPS by examining the effects of visual stimuli approaching the hand and of visual stimuli near the hand. For this purpose, we examined electroencephalograms (EEGs) during a simple reaction time task for tactile stimulus when visual stimuli were presented approaching the hand or were presented near the hand, and we analyzed event-related spectral perturbation (ERSP) as an index of prediction and event-related brain potentials (ERPs) as an index of attention and prediction error. The tactile stimulus was presented to the left (or right) wrist with a high probability (80%) and to the opposite wrist with a low probability (20%). In the approach condition, three visual stimuli were presented approaching the hand to which the high-probability tactile stimulus was presented; in the near condition, three visual stimuli were presented repeatedly near the hand with the high-probability tactile stimulus. Beta band activity at the C3 and C4 electrodes, around the primary somatosensory area, was suppressed before the onset of the tactile stimulus, and this suppression was larger in the approach condition than in the near condition. P3 amplitude for high-probability stimuli in the approach condition was larger than that in the near condition. These results revealed that the approach of visual stimuli facilitates spatial prediction and processing of subsequent tactile stimuli compared to situations in which visual stimuli just exist within the PPS. This study indicated that approaching visual stimuli facilitate the prediction of subsequent tactile events even if they are task-irrelevant.